Welfare of Local Sagu Food Processing Communities in East Kolaka District - Nursalam Nursalam; Kartomo Kartomo; Muhammad Obi Kasmin; Suparman Suparman (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
Processing local food sago is a hereditary activity carried out by some people in the East Kolaka Regency. This activity has been able to provide additional income for the community, so that it has an impact on increasing household income. However, differences in technology and the ability to provide raw materials from each processor ultimately affect differences in the income that can be generated. This research aims to determine the welfare of the local sago food processing community in East Kolaka Regency based on the level of per capita income and income distribution. This research was conducted in August 2023. Location determination was carried out purposively with 68 respondents. The data analysis used is per capita income analysis, which is formulated from the income analysis equation and Gini ratio analysis. The results of the research show that the local sago food processing community in East Kolaka Regency is in the high welfare category, where the per capita income generated by respondents is IDR 7,440,136.-. Gini ratio analysis shows that the Gini ratio coefficient value is 0.58, which means that the level of income inequality in local sago food processing communities in the East Kolaka Regency is in the high category.